P201 Modulating cortical dynamics of binocular rivalry with tRNS over primary visual cortex. Issue 3 (March 2017) - van der Groen, O.; Wenderoth, N.
Abstract : Question: We have recently shown that adding random electrical noise transcranially to the cortex can enhance the detectability of weak visual signals, a phenomenon known as stochastic resonance (SR). However, the concept of stochastic resonance is not only valid for stable systems but can also be used to influence transitions of dynamical systems that consist of multiple attractor states. Here we use binocular rivalry as a model to investigate whether peripherally or centrally added noise influences transitions between different perceptual states. Binocular rivalry is characterized by three naturally occurring attractor states with different stabilities (i.e. seeing the left eye stimulus, the right eye stimulus, or both) and by a spontaneous stochastic switching between these states. This switching is believed to be driven by a combination of neuronal adaptation and noise. Methods: In a series of experiments we presented visual gratings to each eye separately using a mirror stereoscope. Subjects continuously reported whether they perceived the left eye stimulus, the right eye stimulus or a mixed percept. We tested whether switching dynamics were influenced when noise was either added peripherally on the screen or centrally by applying tRNS (100–640 Hz, 1 mA amplitude) to the visual cortex. Results and conclusions: For low contrast stimuli, we found a significantly faster transition from the mixed to the single precepts when noise was added directly to the visual stimulus ( p = 0.03) or to visual cortex using tRNS ( p = 0.02). Our results show that tRNS can be used to modulate the dynamics of cortical processing.